Medicaid professional fees for treatment of opioid use disorder varied widely across states and were substantially below fees paid by medicare in 2021 - Lisa Clemans-Cope; Victoria Lynch; Maya Payton; Joshua Aarons (BMC, 2022)
Abstract Background As Medicaid is the largest payer for opioid use disorder (OUD) treatment services in the United States, information about Medicaid provider reimbursement is critical, and Medicaid payment policies influence the structure of OUD treatment services for everyone with OUD treatment needs. Methods We collected Medicaid professional fees for OUD treatment and related services for the District of Columbia and fifty state Medicaid programs and the Medicare program in 2021. We create three fee indexes related to OUD treatment, with an emphasis on services related to first-line medication treatments in outpatient settings. We then create Medicaid fee indexes and Medicaid-to-Medicare fee indexes. Results Weekly Medicaid fee bundles for methadone treatment at OTPs in 2021 varied widely, more than 4-fold across states. The Medicaid-to-Medicare fee index shows that the national average Medicaid fee bundle was 56 percent of Medicare fees for regular methadone treatment at OTPs in 2021. For services related to OUD treatment, Medicaid fees varied up to 5-fold and larger across the components of each of the four services, and Medicaid fees were low relative to Medicare for almost all state services examined. The Medicaid-to-Medicare fee index was 64 percent of Medicare fees in 2021, ranging from 52 percent for evaluation & management to 76 percent for toxicology testing. Conclusions There appears to be little justification for such large variation in Medicaid fees across states. In addition, the generally low fees in Medicaid persist despite recent efforts to increase access to opioid use disorder treatment for Medicaid enrollees, and have important implications for access to life-saving treatment during the current opioid overdose crisis.